2013
DOI: 10.1152/ajpgi.00263.2012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bile acid receptor TGR5 in gastric adenocarcinoma

Abstract: Bile reflux is a risk factor in the development of intestinal metaplasia in the stomach and is believed to function as an initiator of gastric carcinogenesis. However, whether the G protein-coupled bile acid receptor TGR5 is expressed in this tumor is not known. In this study, we determined the expression of TGR5 in gastric adenocarcinoma and examined the role of TGR5 in cell proliferation. Strong TGR5 staining was present in 12% of cases of intestinal metaplasia but in no cases of normal gastric epithelium (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 22 publications
(30 reference statements)
2
85
0
1
Order By: Relevance
“…siRNA knockdown indicated that DCA-stimulation of ERK1/2 required expression of GPBA and activation of the membrane protease ADAM17, which liberates membrane-tethered heparin-binding EGF-like growth factor, an agonist of the EGF receptor. GPBA is also highly expressed in metastatic gastric adenocarcinoma and taurodeoxycholic acid (TDCA)-induced proliferation of ACS cells requires expression of GPBA (Cao et al, 2013). In the oesophageal adenocarcinoma cell line FLO, GPBA mediates TDCA-stimulated expression of the NADPH oxidase NOX5-S, which is required for the generation of reactive oxygen species and cell proliferation (Hong et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…siRNA knockdown indicated that DCA-stimulation of ERK1/2 required expression of GPBA and activation of the membrane protease ADAM17, which liberates membrane-tethered heparin-binding EGF-like growth factor, an agonist of the EGF receptor. GPBA is also highly expressed in metastatic gastric adenocarcinoma and taurodeoxycholic acid (TDCA)-induced proliferation of ACS cells requires expression of GPBA (Cao et al, 2013). In the oesophageal adenocarcinoma cell line FLO, GPBA mediates TDCA-stimulated expression of the NADPH oxidase NOX5-S, which is required for the generation of reactive oxygen species and cell proliferation (Hong et al, 2010).…”
mentioning
confidence: 99%
“…In the oesophageal adenocarcinoma cell line FLO, GPBA mediates TDCA-stimulated expression of the NADPH oxidase NOX5-S, which is required for the generation of reactive oxygen species and cell proliferation (Hong et al, 2010). In gastric and oesophageal adenocarcinoma cell lines GPBA couples to Gαq, which appears to be necessary for BA-stimulated proliferation (Hong et al, 2010;Cao et al, 2013). GPBA signalling has also been implicated in BA-induced apoptosis of hepatocytes, which can occur during cholestasis.…”
mentioning
confidence: 99%
“…Thus, GPBAR1 could be a marker of tumor aggressiveness. Consistent with this view, Cao et al [20] have shown that moderate to strong GPBAR1 staining in gastric adenocarcinomas associates with decreased patient survival.…”
Section: Discussionmentioning
confidence: 64%
“…By immunohistochemistry GPBAR1 expression in non-neoplastic samples was found to be overexpressed in some patients with intestinal metaplasia [20] when compared with normal gastric epithelium ( Figure 1A). However, the expression of the receptor was not constantly upregulated in gastric adenocarcinoma cells (intestinal and diffuse type), indicating that neither the presence of metaplasia or histologic subtype of the tumor was associated with a specific pattern of GPBAR1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Активация TGR5 способна ин-дуцировать метаплазию эпителия, выявляемую при таком предраковом процессе, как пищевод Барретта [28,31]. Недавнее клиническое исследование по изучению выживаемости пациентов с аденокарциномой желуд-ка, проанализированное с помощью кривых Каплана-Мейера, показало, что чем больше иммунореактивность TGR5 в биоптатах аденокарциномы, тем хуже выжи-ваемость [32]. Приведенные данные свидетельствует о негативном влиянии TGR5 -опосредованных меха-низмов на процессы канцерогенеза верхних отделов же-лудочно-кишечного тракта.…”
Section: канцерогенез апоптоз и пролиферацияunclassified